1989
DOI: 10.1111/j.1365-2125.1989.tb03521.x
|View full text |Cite
|
Sign up to set email alerts
|

Lisinopril dose‐response relationship in essential hypertension.

Abstract: 1 This was a multicentre, double-blind, parallel study in 216 patients with mild to moderate (supine diastolic blood pressure = 95-115 mm Hg) essential hypertension. 2 After a 4-week placebo washout, patients were randomized to placebo or lisinopril 1.25, 5, 20 or 80 mg once daily for 6 consecutive weeks. Supine and erect blood pressure was measured 24 h postdose at the end of weeks -2, 0, 2, 4, and 6. 3 There was a linear dose-response relationship for both supine and erect blood pressure. Diastolic blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…Previous dose titration studies with lisinopril have been conducted in (1) non-diabetic patients with essential hypertension, using BP reductions as the main outcome [2,3]; and (2) patients with non-diabetic nephropathies [9,10]. Lisinopril 40 mg was shown to lower albuminuria and BP more effectively than lisinopril 20 mg. Higher doses have only been tested in essential hypertension studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous dose titration studies with lisinopril have been conducted in (1) non-diabetic patients with essential hypertension, using BP reductions as the main outcome [2,3]; and (2) patients with non-diabetic nephropathies [9,10]. Lisinopril 40 mg was shown to lower albuminuria and BP more effectively than lisinopril 20 mg. Higher doses have only been tested in essential hypertension studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dose titration studies of ACEIs are traditionally conducted according to BP levels in essential hypertension [2,3]. The optimal BP-lowering dose is not, however, necessarily the same as the optimal dose for renoprotection.…”
Section: Introductionmentioning
confidence: 99%
“…No further reduction of urinary albumin excretion rate and BP have been reported when comparing 80 and 160 mg in a 1-yr study of 62 type II patients with microalbuminuria (32). From studies in patients with moderate-tosevere essential hypertension, no evidence of an additional antihypertensive effect of doses of captopril up to 600 mg or enalapril/benazepril up to 80 mg (33)(34)(35)(36) exists. Increasing the dose of valsartan from 80 to 160 mg resulted in an additional drop in systolic and diastolic BP of Ͻ 1 mmHg in mild-to-moderate hypertension (37).…”
Section: Discussionmentioning
confidence: 99%
“…6 Cohen has indicated that this degree in half-tablet weight variability is acceptable since therapeutic outcomes would likely be unchanged. 5 Given the wide therapeutic index of lovastatin 12,13 and lisinopril, 14 it would appear that splitting these 2 products is acceptable. Gee at al.…”
Section: Lovstatin and Lisinopril: Clinical Considerationsmentioning
confidence: 99%